Тривимірний аналіз напружено-деформованого стану металу при правці труб на правильних косовалкових машинах зі спеціальним профілюванням валків - Грибков, Е.П.; Доброносов, Ю.К.; Кухар, В.В.; Малій, Х.В. (Physico-technological Institute of Metals and Alloys, 2024)
In order to increase the competitiveness of domestic metal products, in particular pipes, it is necessary to ensure their compliance with international standards in terms of the main quality indicators. The pipe straightening process provides quality indicators such as straightness and cross-sectional shape. Skew-roll pipe straightening machines are the most common and most effective for straightening pipes of small and medium diameters. The most modern are six-roll pipe straightening machines with special roll profiling, which provide straightening of two types: in the caliber of the profiled rolls and at the step between the roll clamps. But the lack of knowledge about the regularities of straightening pipes holds back the wide implementation of such machines. In the work, a finite element model was developed and with its use, a study of the influence of the straightening process parameters in profiled rolls with symmetric and asymmetric profiling of the extreme pairs of rolls on the indicators of pipe straightness and straightening force was carried out. According to the results of their implementation, it was established that straightening the pipe in gauge and pitch allows to reduce the residual curvature of the pipe by almost three times with a 2.5 times smaller overlapping of the middle rolls relative to the outer ones. At the same time, the force on the most heavily loaded middle rolls increases almost twice, which should be taken into account in view of the possibility of ovality in the section of thin-walled pipes. The use of additional asymmetric profiling of the extreme rolls with step adjustment practically does not affect the quality of straightening in the gauge, increases the quality of straightening at the step by up to 15 %, while reducing the maximum straightening force by 5—7 %. The developed finite-element model allows determining the rational values of rolls overlaps to ensure the minimum residual curvature of the pipes.